Irisin modulates genes associated with severe coronavirus disease (COVID-19) outcome in human subcutaneous adipocytes cell culture - de Oliveira, Miriane; De Sibio, Maria Teresa; Mathias, Lucas Solla; Rodrigues, Bruna Moretto; Sakalem, Marna Eliana; Nogueira, Célia Regina (Molecular and cellular endocrinology, 2020)
Obesity patients are more susceptible to develop COVID-19 severe outcome due to the role of angiotensin-converting enzyme 2 (ACE2) in the viral infection. ACE2 is regulated in the human cells by different genes associated with increased (TLR3, HAT1, HDAC2, KDM5B, SIRT1, RAB1A, FURIN and ADAM10) or decreased (TRIB3) virus replication. RNA-seq data revealed 14857 genes expressed in human subcutaneous adipocytes, including genes mentioned above. Irisin treatment increased by 3-fold the levels of TRIB3 transcript and decreased the levels of other genes. The decrease in FURIN and ADAM10 expression enriched diverse biological processes, including extracellular structure organization. Our results, in human subcutaneous adipocytes cell culture, indicate a positive effect of irisin on the expression of multiple genes related to viral infection by SARS-CoV-2; furthermore, translatable for other tissues and organs targeted by the novel coronavirus and present, thus, promising approaches for the treatment of COVID-19 infection as therapeutic strategy to decrease ACE2 regulatory genes. •Positive effect of irisin on the expression of multiple genes related to viral infection by SARS-CoV-2.•FURIN and ADAM10, associated with increased SARS-CoV-2 replication, are diminished by irisin in human subcutaneous adipocytes.•TRIB3, associated with decreases SARS-CoV-2 replication, is increased by irisin in human subcutaneous adipocytes.